Aggregation behaviour of mixed nonionic-nonionic surfactant solution system - Norjariah, Sahari (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aggregation behavior in mixed system of nonionic-nonionic surfactant solution was studied in this research. The solubility of pyrene in Triton X-100 and Brij 35 at different concentration was evaluated and the critical micelle concentration (cmc) value was then determined from the enhancement of pyrene solubility in these nonionic surfactant solutions. UV spectrometer was used to check the cmc of Triton X-100 and Brij 35 and their mixture. The cmc from single and mixed nonionic surfactant system were compared. From this study, the cmc value of Triton X-100 is 2×10-4M and for Brij 35, the cmc is 8×10-5M. Mixed system of these two nonionic surfactants solutions gave a cmc value of 2×10-5M, which is lower than cmc Triton X-100. The effect of organic solvent (methanol) to the cmc of single and mixed nonionic surfactant solutions was also determined. Addition of 4% of methanol volume from total surfactant solution volume decreased the cmc of Triton X-100 to 1.5×10-4M, Brij 35 to 6×10-5M and for mixed surfactants solution system, decreased to 1.8×10-5M. Increasing more methanol volume (20% methanol added from total surfactant solution) to the solution further decreasing each cmc value and the decreasing in cmc is more obvious. The cmc for Triton X-100 after added 20% methanol is 0.5×10-4M, Brij 35 is 5×10-5M and mixed surfactant solution system is 1.5×10-5M. From this research, we can conclude that mixed surfactant solution system has lower cmc and addition of methanol lowered the cmc value for each single and thus decreased cmc of mixed nonionic surfactant solution system.